The Gospel of Matthew and Christian Judaism : the history and social setting of the Matthean community - Sim, David C. (Studies of the New Testament and its world., 1998)
In this meticulously researched and compelling study, David Sim reconstructs the social setting of the Matthean community at the time the Gospel was written and traces its full history. Dr Sim argues that the Matthean community should be located in Antioch towards the latter part of the first century. He acknowledges the dispute within the early Christian movement and its importance. He defines more accurately the distinctive perspectives of the two streams of thought and their respective relationships to Judaism. A new and important work in Matthean studies.